2017
DOI: 10.1080/00016357.2016.1275038
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study on the impact of orofacial dysfunction on oral health-related quality of life among Brazilian schoolchildren

Abstract: Schoolchildren with orofacial dysfunction experience a greater negative impact on OHRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The results of the simple logistic regression showed that gender and social class had no significant impact on the overall quality of life. Sardenberg et al observed a relatively statistically significant equal impact for gender and TDI on overall OHRQol while lower socioeconomic status had lower significant impact among 8‐ to 10‐year old children . The CPQ 8‐10 questionnaire and the different target age group may explain the reason behind the different results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results of the simple logistic regression showed that gender and social class had no significant impact on the overall quality of life. Sardenberg et al observed a relatively statistically significant equal impact for gender and TDI on overall OHRQol while lower socioeconomic status had lower significant impact among 8‐ to 10‐year old children . The CPQ 8‐10 questionnaire and the different target age group may explain the reason behind the different results.…”
Section: Discussionmentioning
confidence: 95%
“…impact for gender and TDI on overall OHRQol while lower socioeconomic status had lower significant impact among 8-to 10-year old children. 44 The CPQ 8-10 questionnaire and the different target age group may explain the reason behind the different results. The multiple logistic regression model indicated that untreated TDI had a statistically significant impact on overall OHRQoL.…”
Section: Sardenberg Et Al Observed a Relatively Statistically Signifimentioning
confidence: 99%
“…Self‐reported measures are widely employed in oral health research . Despite the advantage of providing accurate results, information derived from personal reports can be compromised by missing responses .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies were cross-sectional [ 9 , 15 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], six studies were case control [ 31 , 32 , 33 , 34 , 35 , 36 ], and three studies were prospective clinical studies [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies [ 15 , 21 , 24 , 25 , 29 , 31 , 32 , 33 , 35 ] evaluated patients with TDI and no TDI, whereas eight studies [ 9 , 26 , 37 , 38 , 39 , 40 , 41 , 42 ] evaluated patients with TDI and after TDI treatment. One study [ 43 ] compared TDI and TDI with treatment needs.…”
Section: Resultsmentioning
confidence: 99%